Tindak Tutur Ilokusi Ujaran Kebencian Dalam Komentar Netizen Di Tiktok - Debi Dwi Rohmatul Aini; Yuniseffendri (Jurnal Ilmu Bahasa, Sastra, dan Budaya, 2026)
This research is motivated by the widespread phenomenon of hate speech on social media, reflecting the degradation of digital language ethics. This study aims to describe the sentence forms and illocutionary functions of hate speech in netizen comments on controversial TikTok content. The method used is descriptive qualitative with a pragmatic approach. Data were collected using the eavesdropping method through the Non-Participatory Observation Technique (Simak Bebas Libat Cakap/SBLC) and note-taking techniques on netizen comments from 15 video contents across three selected accounts between February and April 2026. Data analysis was carried out interactively, including data reduction, data display with specific codification, and drawing conclusions. The results showed that hate speech was expressed through three sentence forms (declarative, interrogative, imperative), with the declarative form being the most dominant. Meanwhile, of Searle's five illocutionary functions, only three functions were found in the data (assertive, expressive, directive), with the assertive function being the most dominant. These findings indicate a close relationship between utterance structure and netizen intentions to attack other parties. This indicates the importance of strengthening digital literacy and content moderation systems that are responsive to covert intentions behind utterances.